Mixed-stack charge transfer crystals of pillar[5]quinone and tetrathiafulvalene exhibiting ferroelectric features - Shivakumar, Kilingaru I.; Swathi, Kadaba; Goudappagouda; Das, Tamal C.; Kumar, Ashwani; Makde, Ravindra D.; Vanka, Kumar; Narayan, Kavassery S.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemistry- A European Journal, 2017)
Ferroelectric materials find extensive applications in the fabrication of compact memory devices and ultra-sensitive multifunctional detectors. Face-to-face alternate stacking of electron donors and acceptors effectuate long-range unidirectional ordering of charge-transfer (CT) dipoles, promising tunable ferroelectricity. Herein we report a new TTF-quinone system-an emerald green CT complex consisting pillar[5]quinone (P5Q) and tetrathiafulvalene (TTF). The CT crystals, as determined by single crystal synchrotron X-ray diffraction, adopt a 1:1 mixed-stack arrangement of donor and acceptor with alternating dimers of TTF and 1,4-dioxane encapsulated P5Q. The TTF-P5Q.dioxane crystal possesses a macroscopic polarization axis giving rise to ferroelectricity at room temperature. The CT complex manifests ferroelectric features such as optical polarization rotation, temperature-dependent phase transition and piezoelectric response in single crystals. Ferroelectric behavior observed in P5Q-based CT complex widens the scope for further work on this structurally intriguing and readily accessible cyclic pentaquinone.
Keywords: Acceptor; Charge-transfer complexes; Chemistry; Conductors; DDQ; Donor; ferroelectric; Macrocycles; Organic Metals; Pi-interaction; Pillar[5]quinone; salts; Transfer Complexes; Transport